Development of an Android-Based Financial Recording and Stock Checking Application for LHJ Kue Cake Shop - Riansyah, Ferdi (UNIVERSITAS KALBIS, 2025)
This study aims to analyze the application of android-based financial applications to the results of the financial statements of LHJ Cake Shop. So far, LHJ Cake Shop often has difficulty in recording finances, the problems that often occur are the length of recording and frequent errors in recording. This research uses the Rational Unified Process (RUP) method as the software development cycle and Android Studio in making the application. To test the application, this research uses blackbox testing and feedback from users. Based on the test results, it is found that financial recording using the Android Financial Application on the smartphone of the owner of the LHJ Cake Shop is proven to facilitate business transactions in the form of purchases-sales, accounts payable, payment of operational expenses and others. Financial reports on Android-based smartphones are easy to use at any time. Real time information in this system helps operations move more effectively and efficiently.